Aplicação de albumina de ovo como substituto de albumina do soro bovino (asb) no cultivo de Leptospira interrogans sorovar Canicola e Pomona - Guedes, I. B.; Souza, G. O.; Castro, J. F. P.; Souza-Filho, A. F.; Heinemann, M. B. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
The main function of Bovine Serum Albumin (BSA) in culture media for Leptospira is protection against the toxic products of the degradation of the long chain fatty acids present in the medium; however, the BSA has a high cost compared to other sources of albumin, such as egg albumin, which is the main protein present in poultry eggs, especially chickens from commercial farms.